Perceptions of HR practices, person–organisation fit, and affective commitment: The moderating role of career stage - Kooij, Dorien T.A.M.; Boon, Corine (Human resource management journal, 2018)
In a three‐wave survey study among 487 Dutch university employees, we examined how and when employees' perceptions of high‐performance work practices (HPWP) affect employee affective commitment. We proposed that perceived person–organisation (PO) fit mediates this relationship and that the relationships among perceptions of HPWP, perceived PO fit, and affective commitment differ across career stages. Our results confirm that perceptions of HPWP enhance PO fit perceptions and, in turn, strengthen affective commitment. Moreover, the relationship between perceptions of HPWP and perceived PO fit is only significant among employees in the advancement stage of their careers; however, direct comparison across different career stages reveals no significant differences in the HPWP–PO fit relationship. Furthermore, career stage partly moderates the relationship between PO fit and affective commitment, which is only significant among employees in the maintenance career stage. These findings have important implications for the literature on strategic Human Resource Management and PO fit.